2022
DOI: 10.2147/cmar.s327621
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxic Breast Cancer Cell-Derived Exosomal SNHG1 Promotes Breast Cancer Growth and Angiogenesis via Regulating miR-216b-5p/JAK2 Axis

Abstract: Background Hypoxia is an important process that involved in the tumor microenvironment. In addition, hypoxic tumor cell-derived exosomes could promote tumor growth and angiogenesis. Thus, we aimed to investigate whether exosomes could regulate tumor development and progression under hypoxia in breast cancer. Methods The level of SNHG1 in hypoxic breast cancer cells and exosomes derived from hypoxic breast cancer cells was determined by real-time qPCR assay. Bioinformati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…MiR-210 was involved in the expression of vascular remodeling related genes, such as Ephrin A3 and PTP1B, which function to promote angiogenesis ( 59 ). In addition to miR-210, lncRNA SNHG1, which was enriched in the hypoxic breast cancer cells secreted exosomes, also promoted the angiogenesis, as well as the proliferation and migration of HUVECs ( 60 ). And some research indicated that hypoxic exosomes were preferentially taken up by hypoxic cancer cells ( 191 ).…”
Section: Hypoxic Exosomes Promote the Development Of Different Types ...mentioning
confidence: 99%
“…MiR-210 was involved in the expression of vascular remodeling related genes, such as Ephrin A3 and PTP1B, which function to promote angiogenesis ( 59 ). In addition to miR-210, lncRNA SNHG1, which was enriched in the hypoxic breast cancer cells secreted exosomes, also promoted the angiogenesis, as well as the proliferation and migration of HUVECs ( 60 ). And some research indicated that hypoxic exosomes were preferentially taken up by hypoxic cancer cells ( 191 ).…”
Section: Hypoxic Exosomes Promote the Development Of Different Types ...mentioning
confidence: 99%
“…Among them, miR-139-5p was reported to interact with SNHG3 in gastric cancer [ 62 ], clear cell renal cell carcinoma [ 64 ], ovarian cancer [ 65 ], and HCC [ 66 ]. SNHG1 sponged miR-216b-5p to promote cell growth and migration in serous epithelial ovarian cancer [ 67 ] and promote tumor angiogenesis and growth in breast cancer [ 68 ]. These findings provide further confirmation that SNHG1 and SNHG3 affect HCC cell behaviors through miRNAs.…”
Section: Resultsmentioning
confidence: 99%
“…[174,181,197] Among these lncRNAs, NORAD, OIP5-AS1, ARSR, SNHG1, and ATB were upregulated in skeletal, urinary, and reproductive system tissues and facilitated cancer development. [175,224,226,239,225] In contrast, the remaining nine lncRNAs (GAS5, LINC01915, LINC00662, FAM225A, SNHG16, LINC00161, SNHG11, CCAT1, and UCA1), GAS5 with LINC01915 were downregulated in respiratory and colorectal cancer, [180,213] the left were upregulated in digestive cancer tissues and promoted oesophageal adenocarcinoma, hepatocellular and pancreatic cancer progression. [187,190,196,201,236,237,248] It is well documented that EVs and miRNAs are irreplaceable intercellular communication tools and have received great attention due to their modulation of angiogenesis.…”
Section: Ev-associated Ncrna-based Regulation Of Cancer-related Angio...mentioning
confidence: 99%